Multimode-enabled silicon photonic delay lines: break the delay-density limit - Shihan Hong; Long Zhang; Jiachen Wu; Yingying Peng; Linyan Lyu; Yinpeng Hu; Yiwei Xie; Daoxin Dai (Light: Science & Applications)
Abstract Integrated optical delay lines have become imperative to meet the growing demand as large aperture antennas and high number of subarrays required for microwave beamforming, high-speed optical communication, and integrated quantum photonics. It is very challenging to achieve large delay ranges, small footprints, and broad bandwidths simultaneously due to the strong trade-off between the propagation loss and the group refractive index of optical waveguides. In this paper, we propose and experimentally demonstrate multimode-enabled silicon photonic delay line for the first time, which breaks the delay-density limit of singlemode waveguide spirals, towards a broadband, mm2-scale, and ultra-large time delay. By demonstrating low-loss-propagation possibilities for different polarizations and modes, we introduce a novel multimode delay unit by integrating the mode (de)multiplexers and the ultralow-loss multimode waveguide spiral supporting the TE0, TE1, and TE2 modes propagating in parallel. The measured propagation losses for the TE0, TE1, and TE2 modes are 0.2 dB/cm, 0.31 dB/cm, and 0.49 dB/cm, respectively. In this way, the highest line delay-density of 376.9 ps/cm and low delay loss of 0.004 dB/ps are achieved. Furthermore, we implement a 7-bit tunable multimode photonic delay line and experimentally demonstrate an ultra-large delay range of 12.7 ns with a delay resolution of 100 ps and within an ultra-compact footprint of 3.85 mm2, enabling a delay density over 3299 ps/mm2, showing the largest delay range and the highest delay density among on-chip delay lines reported to date, to the best of our knowledge.